Targeted inhibition of HER-2 positive breast cancer cells by trastuzumab functionalized pullulan-doxorubicin nanoparticles - Ruiling Xu; Junhui Sui; Mingda Zhao; Yuedi Yang; Lei Tong; Yongmei Liu; Yong Sun; Yujiang Fan; Jie Liang; Xingdong Zhang (Polymer Testing, 2022)
Human epidermal growth factor receptor-2 (HER-2) positive breast cancer is highly invasive with poor clinical outcomes and high risk of recurrence. Here, trastuzumab functionalized pullulan-doxorubicin nanoparticles (Tz-P-Dox) were developed and characterized as a new anticancer formulation for active targeting HER-2 overexpression of breast cancer cells. The obtained nanoparticles had the hydrodynamic diameter of 66.7 ± 2.0 nm and PDI of 0.218 ± 0.012. And the in vitro results showed significant difference of cell uptake and cytotoxic effect between Tz-P-Dox and non-targeted P-Dox against HER-2 positive cell lines (BT474 and MCF-7 cells). However, the differences between Tz-P-Dox and P-Dox were not observed in HER-2 negative cell lines (MDA-MB-231 cells). These results suggested that trastuzumab functionalized nanoparticles had great potential to be considered as a candidate drug for HER-2 positive breast cancer treatment.